Decay chain information on the newly discovered double charm baryon state Ξ++cc; Physical Review D; Vol. 96, iss. 5 - Gutsche T. Thomas; Ivanov M. A. Mikhail; Korner J. G. Jurgen; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich (2017, 2017)
Title screen